The Impact of Social Media Marketing on Brand Loyalty - Amin Rayat; Mehdi Rayat; Layla Rayat (The Society of Aging and Physical Activity (SAPA), 2017)
This article is "Retracted" at 2018/04/04 due to "Plagiarism" totally from "Erdoğmuş, İ. E., & Cicek, M. (2012). The impact of social media marketing on brand loyalty. Procedia-Social and Behavioral Sciences, 58, 1353-1360."